2021
DOI: 10.3389/fcvm.2021.745370
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Outcomes of Bioprosthetic or Mechanical Valve Replacement in End-Stage Renal Disease: A Nationwide Population-Based Retrospective Study

Abstract: Background: Valve replacement is associated with worse outcomes in individuals who have end-stage renal disease (ESRD) and require a long-term renal replacement therapy. Prosthetic valve selection in patients with ESRD has remained controversial.Objective: We aimed to investigate long-term outcomes of mechanical and bioprosthetic valve replacement in individuals with ESRD.Methods: We conducted a population-based retrospective cohort study using data obtained from the Taiwan National Health Insurance Research D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…A mechanical valve is recommended in patients aged <50 years in America and <60 years in Europe, respectively. Large retrospective studies found that biological valves have comparable rates of survival and valve-related reoperation with mechanical valves in ESKD patients who need dialysis, with lower bleeding and thromboembolic events [ 36 , 37 ]. However, calciphylaxis can occur rapidly in a few cases [ 17 , 20 ], and even in patients with biological valves [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mechanical valve is recommended in patients aged <50 years in America and <60 years in Europe, respectively. Large retrospective studies found that biological valves have comparable rates of survival and valve-related reoperation with mechanical valves in ESKD patients who need dialysis, with lower bleeding and thromboembolic events [ 36 , 37 ]. However, calciphylaxis can occur rapidly in a few cases [ 17 , 20 ], and even in patients with biological valves [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, as in the patient presented above, these newer agents are not approved for anticoagulation in patients with mechanical heart valves. Thus in ESRD patients requiring cardiac valve replacement, it is probably prudent, whenever possible, to place bioprosthetic valves, which may have better outcomes in this population anyway 24 …”
Section: Figurementioning
confidence: 99%